Criteria Of Detecting And Selecting Young Talents In Football (u15) - Nahal , Abdallah; Haddada , Mohamed; Nahal , Hamid (sports creativity, 2025)
In this study we went through the subject of using some criteria for detecting and selecting young talents for U15 category in football, to find out if the Chlef state’s coaches rely on them to direct those talented young elements to the discipline that suits their desires and physical abilities, and to improve selection methods in the future. The sample consisted of Chlef league’s football clubs, 16 among which were intentionally picked. The researcher used the descriptive approach (survey method) for it suits this study. To analyze the results, the SPSS V25 statistical program was used to calculate the χ2 values.